2000
DOI: 10.1016/s0014-5793(00)01715-4
|View full text |Cite
|
Sign up to set email alerts
|

Type I muscle atrophy caused by microgravity‐induced decrease of myocyte enhancer factor 2C (MEF2C) protein expression

Abstract: To investigate the molecular mechanisms of muscle atrophy under microgravity, the paraspinal muscles of rats after 14 days spaceflight and those of ground-based controls were examined. In the microgravitational environment, expressions of 42 genes changed, and the expressions of heat shock protein 70 and t complex polypeptide 1 increased. In Northern blotting, myocyte-specific enhancer binding factor 2C (MEF2C) and MEF2C-related genes including aldolase A and muscle ankyrin decreased. After 9 days ground recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
1
14
1
Order By: Relevance
“…These results suggest that, despite elevated levels of Atrogin-1 and MuRF-1 found in muscle of space-flown mice, robust morphological changes distinctive of paraspinal muscle deconditioning are likely just to be set on in mice exposed for 30 days to microgravity. Our present data on mice partially disagree with those of Yamakuchi and co-workers, who described a “qualitative” decrease in the number and volume of type 1 MyHC positive myofibers in paraspinal rat muscle exposed to microgravity for 14 days (Yamakuchi et al, 2000). On the other hand, we expected to find some lower effects of microgravity adaptation in mouse longissimus dorsi compared to the robust changes previously observed in crewmembers after spaceflight or long term bed rest participants, considering the obvious differences in paraspinal muscle loading between bipedal humans and four-legged vertebrates on ground, and in particular during body movement adaptations of both species observed in the microgravity environment.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results suggest that, despite elevated levels of Atrogin-1 and MuRF-1 found in muscle of space-flown mice, robust morphological changes distinctive of paraspinal muscle deconditioning are likely just to be set on in mice exposed for 30 days to microgravity. Our present data on mice partially disagree with those of Yamakuchi and co-workers, who described a “qualitative” decrease in the number and volume of type 1 MyHC positive myofibers in paraspinal rat muscle exposed to microgravity for 14 days (Yamakuchi et al, 2000). On the other hand, we expected to find some lower effects of microgravity adaptation in mouse longissimus dorsi compared to the robust changes previously observed in crewmembers after spaceflight or long term bed rest participants, considering the obvious differences in paraspinal muscle loading between bipedal humans and four-legged vertebrates on ground, and in particular during body movement adaptations of both species observed in the microgravity environment.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, 14-days spaceflight reduced the number of type I muscle fibers, while the expression of 70 kDa heat shock protein, t complex polypeptide 1 and other mitochondrial proteins was upregulated in paraspinal rat muscle. On the other hand, myocyte-specific enhancing factor 2C and aldolase resulted downregulated following spaceflight (Yamakuchi et al, 2000). Recently, the E3-ligase MuRF-1 was found to be increased in longissimus dorsi of mice exposed to microgravity for 30 days (Mirzoev et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When the tissues are under mechanical stresses, cells and tissues adapt to their microenvironment by altering the expressions of specific ECM proteins. For example, lack of mechanical stimulus due to microgravity and prolonged bed rest induces atrophy of muscle, tendon, and bone [116,117]. On the other hand, mechanical overload on cardiac myocytes caused by high blood pressure results in pathological cardiac hypertrophy [118].…”
Section: Applications Of Nanotopography To Tissue Engineering and mentioning
confidence: 99%
“…Haddad et al (44) observed similar results in rats after 9 days in spaceflight, although Baldwin et al (6) found a significant decrease in myofibril protein concentration in slow-twitch muscle fibers, but not fast-twitch, after almost 13 days in spaceflight. Data suggest that spaceflight and hindlimb suspension (HS) cause a selective loss of contractile protein synthesis and slow-to-fast transitions in contractile and regulatory proteins (14,33,69,114,118). Decreased ␤-myosin heavy chain (MHC) protein and mRNA expression has been found in rats under varying time periods of spaceflight and HS (5,37,58,69).…”
Section: Muscle Cellsmentioning
confidence: 99%
“…These results suggest that changes in transcription and translation are responsible for the reduction in protein synthesis. Yamakuchi et al (118) found the expression of 42 genes changed in rats exposed to microgravity. Myocyte-specific enhancer binding factor 2C (MEF2C) and MEF2C-related genes were significantly decreased.…”
Section: Muscle Cellsmentioning
confidence: 99%